Imposing values : an essay on liberalism and regulation - Arnold, N. Scott (Oxford : Oxford University Press, 2009)
'Imposing Values' provides an even-handed characterization of the differences between modern liberalism and classical liberalism about the proper scope of government. It also systematically and comprehensively discusses arguments for and against various regulatory regimes favored by modern liberals and opposed by classical liberals.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Liberalism; Deregulation